Traditional Transport among the Peoples of the Aral Region (1800-1873) - Matjanov Aman (RES MILITARIS, 2022)
The article highlights the history of the development of traditional transport among the peoples of the Aral Sea region: Uzbeks, Kazakhs, Karakalpaks, and Turkmens. The significance of traditional transport in the development of the national economy, trade and culture is revealed.